2012
DOI: 10.15395/mkb.v44n3.85
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Dengue Berat yang Dirawat di Pediatric Intensive Care Unit

Abstract: Virus dengue dapat menyebabkan infeksi pada semua kelompok usia dengan manifestasi klinis beragam mulai dari asimtomatik, ringan, sampai berat yang biasanya merupakan kasus fatal. Dengue berat ditandai dengan kebocoran plasma, hemokonsentrasi, dan gangguan hemostasis. Penelitian ini bertujuan untuk mengetahui karakteristik penderita dengue berat yang dirawat di ruang Pediatric Intensive Care Unit (PICU) RS Dr. Hasan Sadikin Bandung sejak Januari 2009 sampai Desember 2010. Penelitian dilakukan secara retrospekt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A similar report was also found in a previous study conducted at the Central General Hospital of Dr. Sadikin, which reported that almost 60% of children with severe dengue hospitalized for shorter than six days. 24 A cohort study in adult dengue patients found no significant difference in the duration of hospitalization among patients with DF, DHF, and DSS, although there was a trend of increasing duration of hospitalization according to the severity of dengue infection. 27 A fourth-degree DHF patient in this study was hospitalized for fourteen days with complications of sepsis and involvement of the liver, lungs, and systemic.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A similar report was also found in a previous study conducted at the Central General Hospital of Dr. Sadikin, which reported that almost 60% of children with severe dengue hospitalized for shorter than six days. 24 A cohort study in adult dengue patients found no significant difference in the duration of hospitalization among patients with DF, DHF, and DSS, although there was a trend of increasing duration of hospitalization according to the severity of dengue infection. 27 A fourth-degree DHF patient in this study was hospitalized for fourteen days with complications of sepsis and involvement of the liver, lungs, and systemic.…”
Section: Discussionmentioning
confidence: 97%
“…18 The frequency of male affected in this study was more than female, similar to studies in India and Mexico, [19][20][21] but contrary to the studies in the following cities in Indonesia: Yogyakarta, Jakarta, and Bandung. [22][23][24] A study from 6 countries in Asia suggested that the males have a habit of being outdoors which provides a greater opportunity of getting dengue infection due to mosquito bites. 25 However, a previous study showed that there is no difference of immune system response to dengue infection in different gender, evidenced by the same amount of cytokines and antibody produced by female and male dengue patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations